2020
DOI: 10.20883/pielpol.2020.18
|View full text |Cite
|
Sign up to set email alerts
|

Opinia rodziców na temat odmowy wykonania szczepień ochronnych u dzieci

Abstract: Introduction. Preventive vaccinations are the most effective and the cheapest method of fi ghting and preventing infectious diseases. They preclude the development of complications and limit the spread of infections. Over the years, there has been a signifi cant development and growth in disease prevention due to the implementation of preventive vaccination plans, both recommended and compulsory. Aim. The aim of the study was to examine parents' opinions on the refusal of preventive childhood vaccines. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In their study, Szymoniak and co-authors showed that as many as 81% of subjects gained most of their knowledge from healthcare professionals -doctors, nurses and midwives -and from the Internet. Opinions of other parents and medical literature were cited as sources of knowledge by 66% and 41%, respectively [21].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Szymoniak and co-authors showed that as many as 81% of subjects gained most of their knowledge from healthcare professionals -doctors, nurses and midwives -and from the Internet. Opinions of other parents and medical literature were cited as sources of knowledge by 66% and 41%, respectively [21].…”
Section: Discussionmentioning
confidence: 99%
“…This is the most important reason for parents deciding to buy the 5-or 6-component vaccines. A study of Szymoniak et al shows that 52% of Polish parents chose non-reimbursed vaccines instead of those free of charge [12]. Although most European countries finance their compulsory vaccination programmes, Poland is one of the few countries where the 5-or 6-component vaccines are not free [13,14].…”
Section: Discussionmentioning
confidence: 99%